Распространение адолескарий печеночного сосальщика (Fasciola hepatica L.) по пастбищам в засушливое лето - Здун, В.И. (Вестник зоологии, 1971)
The article deals with the materials to characteristic of parasitological situation in
pastures of the western part of Polesie and forest-steppe of the Ukraine. The distribution
of trematode Fasciola hepatica L. adolescarias on pastures in arid summer is compared
with that during a year with an elevated amount of precipitation. Two biotope groups
of mollusks Galba truncatula — an intermediate host of F. hepatica are distinguished: constant and temporary. They are distinguished by dimensions, quantity of mollusks in them
and character of adolescaria dispersion. In an arid period the grazing animal in a decreased astatic biotope swallow at one go hundreds adolescarias, in a constant biotope — single samples. However undrying basins are not less dangerous than periodic ones. Even in arid summer adolescarias have a longer period of viability in them than in astatic, rapidly changing biotopes.